The Influence of Leverage Ratio, Capital Intensity Ratio, and Market Share on the Profitability of Cooperatives in Kediri City - Rani, Shintya Mellinia; Winarko, Sigit Puji; Puspita, Erna (Universitas Nusantara PGRI Kediri, 2024)
Research objectives: This research is motivated by the fact that the profitability obtained in cooperatives varies. This is what attracts investors when they want to invest. Stable profitability will attract investors to invest their capital by seeing how profitability develops each year. To achieve the expected profitability, it is necessary to know the factors that influence profitability. This research aims to determine the effect of the leverage ratio, capital intensity ratio, and market share on the profitability of cooperatives in the city of Kediri. Design/Method/Approach: This research is a type of quantitative causality research. The population used in the research was 317 cooperatives using a purposive sampling technique which used several criteria to obtain a sample of 30. This research used the classical assumption test, multiple linear regression, coefficient of determination test, and hypothesis testing using the SPSS application. Research Findings: The research results show that leverage, capital intensity, and market share partially have a significant effect on profitability. Simultaneously, leverage, capital intensity, and market share have a significant effect on profitability. Based on the results of the analysis and conclusions, the author provides suggestions for investors to pay attention to before investing, for cooperatives it can be used as a guide in increasing cooperative profitability, and for further researchers they can add other variables that can influence cooperative profitability.